2022
DOI: 10.3390/su141912421
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Pathways Used by Pests as Challenges to Plant Health in Agriculture and Forestry

Abstract: Climate change already challenges people’s livelihood globally and it also affects plant health. Rising temperatures facilitate the introduction and establishment of unwanted organisms, including arthropods, pathogens, and weeds (hereafter collectively called pests). For example, a single, unusually warm winter under temperate climatic conditions may be sufficient to assist the establishment of invasive plant pests, which otherwise would not be able to establish. In addition, the increased market globalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 198 publications
0
20
0
Order By: Relevance
“…Reynaud et al (2009) showed that vector abundance (Cicadulina mbila and Peregrinus maidis) and the incidence of viral disease (maize streak virus) were closely related to temperature, increasing rapidly above 24°C, but decreasing above 30°C, a temperature that is detrimental to both the vector and the virus transmission success. This suggests that global warming might promote many insect vectors and the pathogens they transmit, at least within a certain temperature range (Gullino et al, 2022). Aphids are expected to have higher reproductive rates in warmer spring/summer and a higher survival rate in milder winters, which could influence the amount of viral inoculum and the incidence of viral disease transmission and spread (Skendžić et al, 2021), as highlighted in the epidemic of aphid-transmitted viruses in melon crops in Spain (Alonso-Prados et al, 2003).…”
Section: Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynaud et al (2009) showed that vector abundance (Cicadulina mbila and Peregrinus maidis) and the incidence of viral disease (maize streak virus) were closely related to temperature, increasing rapidly above 24°C, but decreasing above 30°C, a temperature that is detrimental to both the vector and the virus transmission success. This suggests that global warming might promote many insect vectors and the pathogens they transmit, at least within a certain temperature range (Gullino et al, 2022). Aphids are expected to have higher reproductive rates in warmer spring/summer and a higher survival rate in milder winters, which could influence the amount of viral inoculum and the incidence of viral disease transmission and spread (Skendžić et al, 2021), as highlighted in the epidemic of aphid-transmitted viruses in melon crops in Spain (Alonso-Prados et al, 2003).…”
Section: Vectorsmentioning
confidence: 99%
“…Climate change is one of several factors presenting an increasingly important threat to ‘plant health’ (Gullino et al., 2022; Hosseinzadeh‐Bandbafha et al., 2023; IPPC Secretariat, 2021; Pautasso et al., 2010). Plant health is a term used to summarize the activities of national plant protection organizations and their legislative and administrative procedures designed to prevent plant pests from entering and spreading within their territories (MacLeod et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, infestations of pests erase 10%–28% of all crop productions 1 . Pesticide sprays and dusts effectively combat infestations in production fields but they lack efficacy in large‐scale crop storage where the interstitial volumes are not easily accessible (e.g., a 9000 mt grain storage silo).…”
Section: Introduction To Fumigationmentioning
confidence: 99%
“…Since the beginnings of agriculture, there has been a struggle to avoid pest populations in order to guarantee our food supply [ 1 , 2 ]. The more abundant, severe and crop-threatening a pest is, the more effort is needed to solve the pest problem [ 3 ].…”
Section: Introductionmentioning
confidence: 99%